EATING DISORDERS IN ADOLESCENTS - Remus RUNCAN; Marius MARICI (Association of Social and Educational Innovation, 2023)
The aim of this study is to review and synthesize peer-reviewed research from scientific journals and books pertaining to eating disorders in adolescents. Our analysis will focus on both typical and atypical eating disorders, including their specific comorbidities, culture-related diagnostic issues, emotional issues, functional consequences, gender distribution, medical consequences, onset, psychosexual effects, symptoms, treatment, and cure. Additionally, we will examine the factors and predictors involved in their aetiology. This study is a crucial step towards advancing Romanian research on eating disorders in adolescents. By thoroughly examining the existing literature, we hope to identify gaps in knowledge and areas for future investigation. Ultimately, our goal is to contribute to the development of effective prevention and treatment strategies for this vulnerable population.